Inhibition of Pseudomonas aeruginosa LPS‐Induced airway inflammation by RIPK3 in human airway. Issue 21 (13th October 2022) - Yun, Minsu; Park, Sun‐Hee; Kang, Dong Hee; Kim, Ji Wook; Kim, Ju Deok; Ryu, Siejeong; Lee, Jeongyeob; Jeong, Hye Min; Hwang, Hye Ran; Song, Kyoung Seob
Abstract: Although the physiological function of receptor‐interacting protein kinase (RIPK) 3 has emerged as a critical mediator of programmed necrosis/necroptosis, the intracellular role it plays as an attenuator in human lungs and human bronchial epithelia remains unclear. Here, we show that the expression of RIPK3 dramatically decreased in the inflamed tissues of human lungs, and moved from the nucleus to the cytoplasm. The overexpression of RIPK3 dramatically increased F‐actin formation and decreased the expression of genes for pro‐inflammatory cytokines (IL‐6 and IL‐1β), but not siRNA‐RIPK3. Interestingly, whereas RIPK3 was bound to histone 1b without LPS stimulation, the interaction between them was disrupted after 15 min of LPS treatment. Histone methylation could not maintain the binding of RIPK3 and activated movement towards the cytoplasm. In the cytoplasm, overexpressed RIPK3 continuously attenuated pro‐inflammatory cytokine gene expression by inhibiting NF‐κB activation, preventing the progression of inflammation during Pseudomonas aeruginosa infection. Our data indicated that RIPK3 is critical for the regulation of the LPS‐induced inflammatory microenvironment. Therefore, we suggest that RIPK3 is a potential therapeutic candidate for bacterial infection‐induced pulmonary inflammation.